Influence of cement thickness on resin-zirconia microtensile bond strength - Lee, Tae-Hoon (The Korean Academy of Prosthodontics, 2011)
PURPOSE: The aim of this study was to evaluate the influence of resin cement thickness on the microtensile bond strength between zirconium-oxide ceramic and resin cement. MATERIALS AND METHODS: Thirty-two freshly extracted molars were transversely sectioned at the deep dentin level and bonded to air-abraded zirconium oxide ceramic disks. The specimens were divided into 8 groups based on the experimental conditions (cement type: Rely X UniCem or Panavia F 2.0, cement thickness: 40 or 160 µm, storage: thermocycled or not). They were cut into microbeams and stored in 37℃ distilled water for 24 h. Microbeams of non-thermocycled specimens were submitted to a microtensile test, whereas those of thermocycled groups were thermally cycled for 18,000 times immediately before the microtensile test. Three-way ANOVA and Sheffe's post hoc tests were used for statistical analysis (α=95%). RESULTS: All failures occurred at the resin-zirconia interface. Thermocycled groups showed lower microtensile bond strength than non-thermocycled groups (P<.001). Differences in cement thickness did not influence the resin-zirconia microtensile bond strength given the same resin cement or storage conditions (P>.05). The number of adhesive failures increased after thermocycling in all experimental conditions. No cohesive failure was observed in any experimental group. CONCLUSION: When resin cements of adhesive monomers are applied over air-abraded zirconia restorations, the degree of fit does not influence the resin-zirconia microtensile bond strength.